DISTRIBUTION AND ESTIMATION OF HEAVY METAL (PB) CONTAMINATION LEVELS IN THE WATER AND SEDIMENT BONDET ESTUARY, CIREBON - Sri Wahyuningsih; Feti Fatimatuzzahroh; Arbi Mei Gitarama (AQUASAINS, 2021)
The water and sediment caused by heavy metal has become a major problem in coastal areas. Heavy metals released into the water binds to particulate matter, accumulate into sediments and its predicted by the pollution assessment method. The aims of this research was to investigate the distribution and contamination levels of Pb in water and sediments of Bondet Estuary. Water and sediments samples were collected from four stations in September 2020. The monitoring data of water quality status, contamination factor (CF), and geo-accumulation index (Igeo) were used to provide a assessment of the Pb contamination. The concentration of Pb in water at all stations (0,024-0,031 mg/L) was higher than the standard surface water, with the status is lightly polluted (class B). CF index for all stations 1 ≤ CF <3 indicates moderate Pb contamination in the sediment, while Igeo for each station is <0, which means no contamination. Overall when referring to some guidelines for sediment standards, Pb concentrations at all stations were still below the standard value for sediment. This study provides a basis for assessing future conditions and risks, so that it can contribute to the management and evaluation of heavy metal contamination in the Bondet Estuary.